2020
DOI: 10.1021/acs.inorgchem.0c02445
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Mechanochromic Luminescence of Tetranuclear Cuprous Complexes

Abstract: Mechanochromic luminescence materials have attracted rapidly growing interest. Nevertheless, the designed synthesis of such materials remains a challenge, and there have been few examples based on weak intramolecular interactions. Herein, we report a new approach for preparing mechanochromic luminescence materials of Cu­(I) complexes, i.e., constructing a photoluminescence system that bears a large coplanar multinuclear Cu­(I) unit showing weak intramolecular π···π interactions with the planar rings of the coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 93 publications
1
25
0
Order By: Relevance
“…The research results indicated that the weak πacid•••base interactions existed between the Cu unit and the carbazole group and the Cu•••Cu interactions played an important role for their turn-on mechanochromism. For tetranuclear Cu(I) complexes, there were many factors that might affect the mechanochromism, such as the change of the Cu•••Cu distance, π-π interactions and the complex geometry (Benito et al, 2014;Peng et al, 2020;Utrera-Melero et al, 2020;Perruchas, 2021). In 2020, Hu's group discovered a supersalt-type Cu(I)-thiolate cluster with irreversible mechanochromism for the first time, which was not completely caused by the CA phase transition (Hu et al, 2020).…”
Section: Multinuclear Cu(i) Complexes With Mechanochromismmentioning
confidence: 99%
“…The research results indicated that the weak πacid•••base interactions existed between the Cu unit and the carbazole group and the Cu•••Cu interactions played an important role for their turn-on mechanochromism. For tetranuclear Cu(I) complexes, there were many factors that might affect the mechanochromism, such as the change of the Cu•••Cu distance, π-π interactions and the complex geometry (Benito et al, 2014;Peng et al, 2020;Utrera-Melero et al, 2020;Perruchas, 2021). In 2020, Hu's group discovered a supersalt-type Cu(I)-thiolate cluster with irreversible mechanochromism for the first time, which was not completely caused by the CA phase transition (Hu et al, 2020).…”
Section: Multinuclear Cu(i) Complexes With Mechanochromismmentioning
confidence: 99%
“…[159,162,176,[202][203][204] The list is not exhaustive and for mechanochromic materials we address the reader to the comprehensive reviews of Sagara et al [150] and Chen et al [205] Moreover, several innovative molecular systems which can display different colors upon change of conformation or crystal structures, could expand the scope of mechanochromic materials in the near future, making more colorations available and improving the performances of the materials in terms of sensibility and reliability. [206][207][208][209][210][211][212] Applications such as sensors, displays, memories, optical waveguides for hydrostatic or flex measurements, and light-emitting fabrics, [151,186,204,[213][214][215][216][217] represent a solid foundation for the spreading of mechanoresponsivity in the robotic communities. The self-healing properties found in several of the aforementioned systems are also of particular interest for soft robotics.…”
Section: From Cromatophore As Absorbance Elements Through Molecular Mechanochromic Devicesmentioning
confidence: 99%
“…)-2.7229(11) Å and Cu-P: 2.2598(10)-2.292(3) Å), and this suggests stronger chelating abilities in three-coordinate Cu(I) halide complexes as a result of the introduction of ethynyl. The introduction of electron-rich CRC will increase the conjugation of the whole molecule and the electron density of the P atoms, and the P atoms are more easily coordinated with Cu(I).…”
mentioning
confidence: 94%
“…Cu(I) complexes have received particularly wide attention as a promising alternative to phosphorescent complexes based on noble metals such as iridium or platinum due to their excellent luminescence, high abundance and low price. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] When Ma and his colleagues first reported a highly luminescent tetranuclear complex Cu 4 (CRCph) 4 L 2 (L = 1,8-bis(diphenylphosphino)-3,6-dioxaoctane) as an emitting layer in EL devices, it opened a door to Cu(I) complexbased fabrication of OLEDs. 18 Compared with phosphorescent (triplet harvesting) materials, thermally activated delayed fluorescence (TADF, singlet harvesting) materials are designed to display a very small energy gap DE(S 1 -T 1 ), but under thermal activation, reverse ISC from the lowest excited triplet (T 1 ) to the lowest excited singlet (S 1 ) is possible.…”
Section: Introductionmentioning
confidence: 99%